Pengaruh Inokulasi Mikoriza terhadap Komponen Hasil Padi Sistem Pengairan Aerobik yang Ditumpangsarikan dengan Kacang Hijau - Wayan Wangiyana; I Gusti Putu Muliarta Aryana; I Gde Ekaputra Gunartha; Ni Wayan Dwiani Dulur (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
This study was aimed to examine effect of inoculation with Arbuscular Mycorrhizal Fungi (AMF) and intercropping with several mungbean varieties on yield components of red rice grown under aerobic irrigation technique. The experiment was carried out in a pot in the plastic house from June to September 2017. The experiment was designed using Completely Randomized Design with two treatment factors arranged factorially, i.e. AMF inoculation (M0= without, or M1= with AMF inoculation) and mungbean varieties (V) grown together with red rice plant (V1= Kenari, V2= Vima-1, V3= Vima-3, V4= Merak, and V5= No. 129 ). Each treatment combination was made in triplicate. The results indicated that inoculation had a significant effect in increasing filled panicle number, number of filled grains, and dry grain yield per pot, while decreasing percentage number of unfilled grains. For the rice plants incoluated with AMF, intercropping with mungbean of Kenari and Merak varieties produced similar or higher number of filled panicles compared to those without intercropping. In contrast, for the rice plant without inoculation with AMF, intercropping resulted in lower amount of filled panicles than those without intercropping.